An exploration of social work needs of select rural behavioral health agencies in Washington state. Issue 6 (1st November 2016) - Beecher, Blake; Reedy, Amanda Rose; Loke, Vernon; Walker, Jenna; Raske, Martha
ABSTRACT: Mental health disorders rank among the top five chronic illnesses in the United States and counties and states across the nation struggle to provide effective services to address these disorders. In order to design and deliver mental health education and training tailored to meet regional needs, an assessment of the staff training and education needs of three rural behavioral health centers in Washington State was conducted. The purpose of this qualitative study was to explore the service and staffing patterns, educational and training needs, and strengths as well as barriers to providing a professionally trained behavioral health workforce. Findings indicate both strengths and challenges for rural behavioral health agencies and include: (1) place/setting themes, (2) practice themes, (3) policy themes, and (4) training needs and opportunities. Rural behavioral health agencies need social workers who have generalist knowledge and training in a range of theories and skills, particularly in evidence-based treatments and crisis intervention.